Divorce Lawsuit against Unrecorded Marriages Post Sema Number 3 Year 2018 - Purba, Mariah SM; Nainggolan, Rosita; Hermes, Christian Daniel; Sinaga, Dhea Rosarni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Issuance of Supreme Court Circular Letter (SEMA) No. 3 of 2018 which states that "divorce where the marriage is not registered in the civil registry against a divorce lawsuit filed in court, can be accepted and granted, as long as the marriage was solemnized according to religion/custom before the enactment of Law Number 1 of 1974, has made the marriage registration at the Civil Registry office is a condition for the validity of the marriage and/or a condition for filing for divorce in accordance with statutory provisions. The problem raised in this research is whether the Supreme Court Circular (SEMA) No. 3 of 2018 can be used as a basis for deciding divorce lawsuits that are not registered in the civil registry against divorce lawsuits filed in court, as long as the marriage was solemnized according to religion/custom before the enactment of Law Number 1 of 1974 in conjunction with Government Regulation No. 9 of 1975?. The research method used in this research is the normative juridical legal research method. The approaches used in this research are the statutory approach and the conceptual approach. The legal data used in this research are primary legal materials and secondary legal materials.